Period poverty behind the numbers: gender, race, and class in the menstrual experiences of girls from an urban periphery in Brazil - Januária Monteiro Menegotto; Fernanda Bittencourt Ribeiro (Tapuya)
This article analyzes period poverty based on interviews with six girls living in a region on the outskirts of the city of Porto Alegre (Brazil). The results of the qualitative study reveal some realities that are behind the numbers. The lack of information about menstrual health, menstrual cycles, and the limited self-awareness about the body became evident. All the interviewed adolescents who sought health services due to any menstrual or body-related issues during puberty received a racist, sexist, or ageist treatment or a combination of these prejudices. Their accounts regarding access to menstrual hygiene products and sanitation infrastructure do not fully correspond to the data on period poverty: the girls have access to disposable sanitary pads during menstruation, clean water, and bathrooms in usable conditions. The stories told by the teenagers expand the discussion about period poverty as they highlight cultural factors related to their menstrual experiences. Their accounts also show that initiatives and public policies to combat menstrual precariousness cannot be limited to the material field and point to the need for systemic cultural changes to combat racism, sexism, and ageism.